Analisis pengaruh modal usaha, umur, pendidikan dan jam kerja terhadap pendapatan pedagang pasar tradisional di Desa Sungai Saren Kecamatan Bram Itam Kabupaten Tanjung Jabung Barat - Selamat Rianto; Zulgani Zulgani; Purwaka Hari Prihanto (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study aims to analyze the effect of capital, age, education and working hours on the income of traditional market traders in Sungai Saren Village, Bram Itam District, Tanjung Jabung Barat Regency. The data used in this study are primary data, the sampling method used in this study is Purposive Sampling with 56 respondents as traders, the analytical tool used is Multiple Linear Analysis.Based on the results of the study obtained a probability value of 0,000 for the F Test and partial test of Capital, Age, Education and Working Hours variables. This shows that the variables simultaneously and partially all the variables have a significant effect on the income of Traders in the Traditional Market of Sungai Saren, Bram Itam District, Tanjung Jabung Barat Regency. Determination Coefficient Value (R2) of 0.520 shows that the influence of Capital, Age, Education and Working Hours, Work on the income of Traders of Sungai Saren Market, Bram Itam District, Tanjung Jabung Barat Regency is 52%.